A multifaceted strategy for implementation of the Ottawa ankle rules in two emergency departments. (12th August 2009) - Bessen, Taryn; Clark, Robyn; Shakib, Sepehr; Hughes, Geoffrey
Abstract : Problem Despite widespread acceptance of the Ottawa ankle rules for assessment of acute ankle injuries, their application varies considerably. Design Before and after study. Background and setting Emergency departments of a tertiary teaching hospital and a community hospital in Australia. Key measures for improvement Documentation of the Ottawa ankle rules, proportion of patients referred for radiography, proportion of radiographs showing a fracture. Strategies for change Education, a problem specific radiography request form, reminders, audit and feedback, and using radiographers as "gatekeepers." Effects of change Documentation of the Ottawa ankle rules improved from 57.5% to 94.7% at the tertiary hospital, and 51.6% to 80.8% at the community hospital (P<0.001 for both). The proportion of patients undergoing radiography fell from 95.8% to 87.2% at the tertiary hospital, and from 91.4% to 78.9% at the community hospital (P<0.001 for both). The proportion of radiographs showing a fracture increased from 20.4% to 27.1% at the tertiary hospital (P=0.069), and 15.2% to 27.2% (P=0.002) at the community hospital. The missed fracture rate increased from 0% to 2.9% at the tertiary hospital and from 0% to 1.6% at the community hospital compared with baseline (P=0.783 and P=0.747). Lessons learnt Assessment of case note documentation has limitations. Clinician groups seem to differ in their capacity and willingness to change their practice. A multifaceted change strategy including a problem specific radiography request form can improve the selection of patients for radiography.